Effect of Maternal Obstructive Sleep Apnea-Hypopnea on 24-Hour Blood Pressure, Nocturnal Blood Pressure Dipping and Arterial Stiffness in Hypertensive Disorders of Pregnancy - Panyarath, Pattaraporn; Goldscher, Noa; Pamidi, Sushmita; Daskalopoulou, Stella S.; Gagnon, Robert; Dayan, Natalie; Raiche, Kathleen; Olha, Allen; Benedetti, Andrea; Kimoff, R. John (Frontiers in Physiology, 2021)
Rationale: Maternal obstructive sleep apnea-hypopnea (OSAH) is associated with hypertensive disorders of pregnancy (HDP). Attenuation of the normal nocturnal blood pressure (BP) decline (non-dipping) is associated with adverse pregnancy outcomes. OSAH is associated with nocturnal non-dipping in the general population, but this has not been studied in pregnancy. We therefore analyzed baseline data from an ongoing RCT (NCT03309826) assessing the impact of OSAH treatment on HDP outcomes, to evaluate the relationship of OSAH to 24-h BP profile, in particular nocturnal BP dipping, and measures of arterial stiffness. Methods: Women with a singleton pregnancy and HDP underwent level II polysomnography. Patients with OSAH (AHI ≥ 5 events/h) then underwent 24-h ambulatory BP monitoring and arterial stiffness measurements (applanation tonometry, SphygmoCor). Positive dipping was defined as nocturnal Systolic BP (SBP) dip ≥10%. The relationships between measures of OSAH severity, measures of BP and arterial stiffness were evaluated using linear regression analyses. Results: We studied 51 HDP participants (36.5±4.9y, BMI 36.9±8.6kg/m2) with OSAH with mean AHI 27.7±26.4 events/h at 25.0±4.9 weeks’ gestation. We found no significant relationships between AHI or other OSA severity measures and mean 24-h BP values although BP was generally well-controlled. Most women were SBP non-dippers (78.4%). AHI showed a significant inverse correlation with % SBP dipping following adjustment for age, BMI, parity, gestational age, and BP medications (β =-0.11, p=0.02). Significant inverse correlations were also observed between AHI and DBP (β =-0.16, p=0.01) and MAP (β =-0.13, p=0.02) % dipping. Oxygen desaturation index and sleep time below SaO2 90% were also inversely correlated with % dipping. Moreover, a significant positive correlation was observed between carotid-femoral pulse wave velocity(cfPWV) and REM AHI (β=0.02, p=0.04) in unadjusted but not adjusted analysis. Conclusions: BP non-dipping was observed in a majority of women with HDP and OSAH. There were significant inverse relationships between OSAH severity measures and nocturnal % dipping. Increased arterial stiffness was associated with increasing severity of OSAH during REM sleep in unadjusted although not adjusted analysis. These findings suggest that OSAH may represent a therapeutic target to improve BP profile and vascular risk in HDP.